The Intensification of surveillance : crime, terrorism and warfare in the information age - Ball, Kirstie; Webster, Frank (Pluto Press, 2003)
Shocking expose of surveillance methods. Shows how we can combat crime without eroding civil liberties.
Keywords: Privacy, Right of.; Electronic surveillance -- Social aspects.; Social control.; War on Terrorism, 2001-2009.; Operation Enduring Freedom, 2001-2014.; Social Control, Formal; Droit à la vie privée.; Surveillance électronique -- Aspect social.; Contrôle social.; Opération Liberté immuable, 2001-2014.; Guerre contre le terrorisme, 2001-2009.; LAW -- Forensic Science.; POLITICAL SCIENCE -- Human Rights.; Electronic surveillance -- Social aspects; Privacy, Right of; Social control; 2001-2009